Multiple Comorbidities and Interest in Research Participation Among Clients of a Nonprofit Food Distribution Site. Issue 5 (17th August 2015) - Higashi, Robin T.; Craddock Lee, Simon J.; Leonard, Tammy; Cuate, Erica L.; Cole, Jay; Pruitt, Sandi L.
Abstract: Background: Persons accessing food from nonprofit distribution sites face numerous challenges and typically have significant unmet health needs. However, given limited and intermittent healthcare system engagement, this vulnerable population is underrepresented in clinical research. We sought to better understand the health needs of a nonclinical population to inform future research and interventions. Methods: : Focus groups were conducted in English ( n = 4) and Spanish ( n = 4) with clients of Crossroads Community Services (CCS), the largest distributor of North Texas Food Bank. Discussions probed participants' health status, healthcare utilization, understanding and utilization of mammography, and attitudes toward participation in research. Results: Participants included 42 CCS clients, primarily Hispanic or African American women. Participants reported multiple comorbid conditions among household members, yet utilization of health services was often limited by cost. The majority expressed interest in participating in research to communicate their health concerns and obtain emotional support. Conclusion: CCS clients represent a high‐need, under‐reached population willing to engage in health‐related research that affords them opportunity to connect with peers in group settings and obtain information to improve management of daily life challenges. The Community Assistance Research (CARe) Initiative, a community–academic collaboration, establishes a much‐needed opportunity for ongoing clinical research and intervention among this underserved population.